1999
DOI: 10.5860/crl.60.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Publish or Perish: A Dilemma For Academic Librarians?

Abstract: This study examines the influence of scholarly requirements on librar ians' ability to earn tenure or continuous employment. After a literature review, the authors present the results of a survey of research, doctoral, and master's-level institutions. Of the 690 responding institutions, 54.3 percent employ tenure-track librarians. Of these, more than 60 percent require some scholarship and 34.6 percent encourage it. At these 374 institutions, 92.2 percent of librarians who underwent tenure review dur ing a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 17 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…34 Recall the studies by Mitchell and Reichel and Mitchell and Swieszkowski, which found that librarians are gaining tenure without publishing, whether through substituting service or by having the publication requirement waived entirely. 35 If librarians do not feel the same pressure to publish as instructional faculty do, and if librarians are indeed migrating to blogging, it might explain the decrease in authorship documented by Wiberly, Hurd, and Weller. Indeed, the rapid growth of the blogosphere after 2001 has been documented and falls within the timeframe of Wiberly, Hurd, and Weller's 2006 study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Recall the studies by Mitchell and Reichel and Mitchell and Swieszkowski, which found that librarians are gaining tenure without publishing, whether through substituting service or by having the publication requirement waived entirely. 35 If librarians do not feel the same pressure to publish as instructional faculty do, and if librarians are indeed migrating to blogging, it might explain the decrease in authorship documented by Wiberly, Hurd, and Weller. Indeed, the rapid growth of the blogosphere after 2001 has been documented and falls within the timeframe of Wiberly, Hurd, and Weller's 2006 study.…”
Section: Discussionmentioning
confidence: 99%
“…Gillum argued that "without the lure of promotion and tenure, there is little motivation for librarians to contribute to the body of LIS literature." 26 Joseph Fennewald found that a recurring theme motivating those academic librarians who do publish was the belief that "the importance of research is to identify new knowledge that will enhance practice." 27 Advocates for continued librarian scholarship echo this theme.…”
mentioning
confidence: 99%
“…Much of this cohort mentoring would also fall under the auspices of peer mentoring. At "first glance, the term peer mentoring might seem somewhat of a paradox given that mentoring is normally associated with expert-novice relationships" (Le Cornu, 2005, p. 356), but having a tight-knit peer group can engender a sense of community, trust, and career success for everyone involved, which can build the confidence to overcome some of the obstacles inherent to librarians in the "publish or perish" environment of academia (Mitchell & Reichel, 1999). However, group and peer mentoring can still suffer some of the failures mentioned by Goldstein (2003) if insecurities or intimidation arise if one member advances more quickly in his or her career than the others.…”
Section: Alternatives To Traditional Mentoringmentioning
confidence: 99%
“…A study by Emily Werrell and Laura Sullivan (1987) states that 79 percent of academics have some form of faculty status and, therefore, must pursue activities such as research, publication, and professional service. A more recent survey of research, doctoral and master's level institutions shows that 54.3 percent have tenure-track librarians (Mitchell and Reichel, 1999). The literature is abundant with articles on issues related to publishing and tenure, including Janet Swan Hill's article on librarians as faculty members (1994); W. Bede Mitchell and L. Stanislava Swieszkowski's article on publication requirements and tenure approval rates (1985); Robert Boice, Jordan M. Scepanski and Wayne Wilson's publication on coping with pressures to publish (1987); and Bradigan and Mularski's analysis of publication requirements for tenure and promotion (1996).…”
Section: Professional Development and Reference Librariansmentioning
confidence: 99%